Analisis Kinerja Keuangan Dengan Menggunakan Rasio-Rasio Keuangan dan Economic Value Added (EVA) pada PT. Bank Muamalat Indonesia tbk. - Ahmad Mukhlis; Novanda Puspha Zahra (Majalah Ilmiah Bijak, 2019)
The purpose of this study is to determine the financial performance of Muamalat Indonesia Tbk. bank by using financial ratios and Economic Value Added (EVA) period 2013-2017. The research is a type of qualitative research with descriptive method.As for the results of the study is the highest ROA value is in the year 2013 because it is above the standard, the value of bank ROE tends to decline from year to year, the value of NPM bank fluctuate every year, the CAR value of the bank can categorized well because it is always above standard, DER and DAR fluctuate every year, while positive EVA values are only in 2015